SEISMIC ATTRIBUTES FOR CHANNEL INTERPRETATION AND FACIES MODELING: A CASE STUDY OF Y FIELD, MALAY BASIN - BIN ROSLAN, MOHD RAIS RASEDY (Universiti Teknologi PETRONAS, 2014)
This project focuses on the improvement of facies modeling methodology by incorporating seismic interpretation of channel geometries and orientations for group I reservoir in Y field, Malay basin. Object based modeling technique is used to populate discrete facies model with different bodies using the geometries interpreted from the seismic. In order to improve channel interpretation in seismic, various attributes such as sweetness and variance (opposite to coherency) were used. All the seismic interpretation and facies modeling workflow were conducted in PETREL™. Apart from PETREL project, a geological field mapping was also carried out to map the distribution of exposed channel levee outcrop in Bukit Merah, Perak. The key methodologies in this project are data gathering, seismic interpretation, structural modeling, facies modeling as well as analogue mapping. Indeed, by incorporating detailed channel geometries interpreted from seismic into facies modeling, it results in a more accurate and geologically sound facies model